The Effect of Family Financial Socialization on Financial Self-Efficacy Mediated by Financial Knowledge and Financial Skills - April, Reza; Chandra, Novrina; Fontanella, Amy; Sukartini, Sukartini (International Ecsis Association, 2024)
This study aims to explore and provide empirical evidence on how financial socialization directly affects financial knowledge, financial skills, and financial self-efficacy. Additionally, it investigates the relationships between financial knowledge, financial skills, and financial self-efficacy, while also examining the indirect influence of financial socialization on financial self-efficacy through the mediation of financial knowledge and skills. The research focused on a sample of 208 millennials from West Sumatra, selected through non-probability accidental random sampling. The data analysis utilized the partial least square structural equation modeling technique (SEM PLS) with SmartPLS 3.0. The findings revealed that the direct impact of financial socialization on financial knowledge and skills was statistically significant. However, the direct effect of financial socialization on financial self-efficacy was not deemed significant. The study also established the statistically significant impacts of financial knowledge and financial skills on financial self-efficacy, along with confirming the indirect influence of financial socialization on financial self-efficacy through the mediation of financial knowledge and skills.